2009
DOI: 10.1136/jech.2008.074542
|View full text |Cite
|
Sign up to set email alerts
|

Maternal glucose tolerance status influences the risk of macrosomia in male but not in female fetuses

Abstract: There is sexual dimorphism in the risk of abnormal birth weight attributed to maternal glucose tolerance status. A closer surveillance of foetal growth might be warranted in pregnant women with abnormal glucose tolerance carrying a male fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
2
41
2
Order By: Relevance
“…The 20 studies [1,3,4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] that met inclusion criteria provide data on 2,402,643 women. A study from Retnakaran and Shah [4] evaluated the risk for GDM conferred by fetal sex in a first pregnancy and, in those women in whom it was applicable, the analogous risk in a second pregnancy such that, in the pooled analyses, the first and second pregnancies from this study were entered as two separate reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 20 studies [1,3,4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] that met inclusion criteria provide data on 2,402,643 women. A study from Retnakaran and Shah [4] evaluated the risk for GDM conferred by fetal sex in a first pregnancy and, in those women in whom it was applicable, the analogous risk in a second pregnancy such that, in the pooled analyses, the first and second pregnancies from this study were entered as two separate reports.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we performed a sensitivity analysis based on the stringency of the diagnostic approach for identifying GDM that was applied in the studies. In this analysis, we included only the seven studies [1,3,18,25,[28][29][30] that used the two-step approach to diagnose GDM (i.e. screening test followed by an OGTT) that was recently recommended by the National Institutes of Health (NIH) Consensus Panel [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] It is well known that male sex is a risk factor for worse perinatal outcomes in the general obstetric population, 7 with increased risk of preterm delivery, 8 labor dystocia, 9 cord problems, 10 instrumental vaginal deliveries or cesarean section (CS), 10,11 macrosomia, 10 low Apgar scores, 10 major birth defects, 1 and perinatal mortality. 2,8,12 In relation to diabetic pregnancy, fetal sex has been considered only occasionally. In 1996, Bracero et al 3 reported that male sex was an independent predictor of higher risk for hypoglycemia and for stay in the neonatal intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…3 While maternal weight appeared positively related with macrosomia in both sexes and negatively with growth retardation in male fetuses, gestational DM was associated with macrosomia exclusively in male offspring. 21 Among siblings of patients with T1DM, a greater secondary attack rate of T1DM at older ages was found in males than in females. 22 Paternal, but not maternal, age at T1DM onset might be a predictor of T1DM recurrence in offspring.…”
Section: Fetal Programming and Geneticsmentioning
confidence: 98%